Influence of processing parameters on the densification and the microstructure of pure zinc oxide ceramics prepared by spark plasma sintering. Issue 8 (1st June 2019) - Radingoana, P.M.; Guillemet-Fritsch, S.; Olubambi, P.A.; Chevallier, G.; Estournès, C.
Abstract: Due to the sensitivity of nanopowders and the challenges in controlling the grain size and the density during the sintering of ceramics, a systematic study was proposed to evaluate the densification and the microstructure of ZnO ceramics using spark plasma sintering technique. Commercially available ZnO powder was dried and sintered at various parameters (temperature (400–900 °C), pressure (250–850 MPa), atmosphere (Air/Vacuum) etc.). High pressure sintering is desirable for maintaining the nanostructure, though it brings a difficulty in obtaining a fully dense ceramic. Whereas, increasing the temperature from 600 to 900 °C results in fully densified ceramics of about 99% which shows to have big impact on the grain size. However, a high relative density of 92% is obtained at a temperature as low as 400 °C under a pressure of 850 MPa. The application of pressure during the holding time seems to lower the grain size as compared to ceramics pressed during initial stage (room temperature).